Experimental Investigation of Crumb Rubber Concrete Columns under Seismic Loading. (August 2015) - Youssf, Osama; ElGawady, Mohamed A.; Mills, Julie E.
Abstract: Crumb rubber concrete (CRC) is a class of concrete that incorporates crumb rubber from used tyres as a partial replacement for the natural aggregates in conventional concrete. Previous research at the material level has shown that the rubber can improve the ductility, damping ratio, and energy dissipation properties of concrete, which are the most important parameters in concrete structures that are subjected to earthquake loads. However, CRC can have lower compressive strength when compared with conventional concrete. This paper describes experimental work conducted to explore the possible use of CRC for structural columns. Three reinforced concrete columns having 240 mm diameter and 1500 mm shear span were tested under axial compression load and incrementally increasing reversed cyclic loading. One column was constructed out of CRC and the other two were constructed out of conventional concrete but subjected to different axial loads. A snap-back test was conducted to evaluate the damping properties of each column. The results indicated that the use of CRC increased the hysteretic damping ratio and energy dissipation of the columns by 13% and 150% respectively. However, CRC decreased the viscous damping ratio compared to a conventional concrete column. The CRC column was able to sustain a lateral load and ultimate drift of about 98.6% and 91.5%, respectively, of those sustained by the conventional column. This investigation demonstrates that CRC provides an environmentally-friendly alternative to conventional concrete in structural applications.